2020
DOI: 10.1002/fsn3.1610
|View full text |Cite
|
Sign up to set email alerts
|

A study on genotype–environment interaction based on GGE biplot graphical method in sunflower genotypes (Helianthus annuus L.)

Abstract: GGE biplot technique is one of the appropriate methods for investigating the genotype–environment interaction. An experiment was conducted to examine and evaluate the stability and adaptability of grain yield of 12 sunflower genotypes using the randomized complete block design (RCBD) with three replications in five regions including Karaj, Birjand, Firooz‐Abad, Kashmar, and Arak within two agricultural years. Analysis of variance indicated that the effect of location, year, location × year, genotype, and genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 18 publications
4
14
0
Order By: Relevance
“…In our study, soybean lines 2, 5, 6, and 7 were identified as desirable due to their proximity to the ideal genotype. This finding aligns with the work of Ansarifard et al (2020) and Stansluos et al (2023), who employed the GGE biplot for evaluating and selecting outstanding genotypes based on various agronomic traits. While the outcomes of parametric stability analysis methods largely concurred with the GGE biplot analysis, additional stability approaches were necessary to categorize stable lines and reinforce our results.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, soybean lines 2, 5, 6, and 7 were identified as desirable due to their proximity to the ideal genotype. This finding aligns with the work of Ansarifard et al (2020) and Stansluos et al (2023), who employed the GGE biplot for evaluating and selecting outstanding genotypes based on various agronomic traits. While the outcomes of parametric stability analysis methods largely concurred with the GGE biplot analysis, additional stability approaches were necessary to categorize stable lines and reinforce our results.…”
Section: Discussionsupporting
confidence: 91%
“…Although MET primarily focus on identifying superior genotypes for target environments, established breeding programs also apply MET to generate relevant information about tested environments (Gauch and Zobel, 1997;Yan et al, 2000;Yan and Kang, 2002;Laffont et al, 2013;Gauch, 2013;Yan, 2015Yan, , 2016. This analysis can be useful to identify mega-environments (ME) across a wider production area (Rakshit et al 2012;Nielsen and Vigil 2018;Dalló et al 2019;Sharma et al 2020;Ansarifard et al 2020) A common breeding approach for multinational commercial breeding programs is to cross elite germplasm adapted to diverse target environments (Cooper et al, 2014). Studies have demonstrated the potential advantages of utilizing this strategy in hybrid crops (Podlich and Cooper, 1998;Technow et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It can interpret the interaction between different traits of a cultivar and is often used for analyzing the interaction effect of multi-environment tests 13,21 in wheat, 22 maize, 23 rice, 24 bean, 25 oats, 26 Papaver somniferum L., 27 Pisum sativum L., 28 sorghum, 7,29 and sunflower. 30 In cotton, the GGE biplot has been used to assort the cotton production areas into different ecological regions in Spain 31 and to differentiate the ecological regions of cotton fiber quality in Northwest Inland (NWI) in China. 32 It was also used to analyze the lint yield and fiber traits of cultivars and evaluate the performance of experimental stations in a regional experiment in the Yangzi River Valley (YaRV).…”
Section: ■ Introductionmentioning
confidence: 99%
“…GGE biplot is a novel tool for studying the effect of genotype, environment, and G×E that displays the optimum planting area of a cultivar simply and intuitively via a two-dimensional plot. It can interpret the interaction between different traits of a cultivar and is often used for analyzing the interaction effect of multi-environment tests , in wheat, maize, rice, bean, oats, Papaver somniferum L., Pisum sativum L., sorghum, , and sunflower . In cotton, the GGE biplot has been used to assort the cotton production areas into different ecological regions in Spain and to differentiate the ecological regions of cotton fiber quality in Northwest Inland (NWI) in China .…”
Section: Introductionmentioning
confidence: 99%